Containing Madness Gender and 'Psy' in Institutional Contexts (Springer International Publishing, 2018)
This collection explores the discursive production and treatment of mental distress as it is mediated by gender and race in different institutional contexts. Featuring analyses of the prison, the psychiatric hospital, immigration detention, and other locales, this book explores the multiple interlocking oppressions that result in the diagnosis and medical, psychological, and psychiatric treatment of individuals constituted as 'mentally ill' at various historical moments and across institutional spaces. Contributors unpack how feminine, masculine, and transgender bodies are made up as mentally ill/sick/deviant by way of biomedical and institutional knowledges and discourses and are intervened upon by different institutional and expert authorities.